The Application of Strategic Renewal Mechanisms in the Process of Organisational Boundary Management - Cyfert, Szymon (Wykorzystanie mechanizmów odnowy strategicznej w procesie zarządzania granicami organizacji, 2010)
The aim of this paper is to discuss the possibilities of applying strategic renewal mechanisms in the process of organisational boundary management. The starting point of the article is a presentation of the fundamental assumptions in the conception of organisational boundaries followed by a presentation of the mechanisms and models of strategic renewal, on the basis of which the author then formulates his own proposal for a model of the strategic organisational boundary renewal process.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 39-47
Keywords: strategic renewal of organisations; models of strategic renewal; organisational boundaries